A kifejezés és befogadás boldog lehetetlensége: Mítosz és újrajátszás Süli-Zakar Szabolcs Sziszüphosz című kísérleti videóinstallációjában - Kovács, Edward (Studia Litteraria, 2024)
This study explores the possible correlations between the aesthetic procedures of artistic re-enactments as a critical re-translations and performative modes of recontextualizing the events of the past and the mythical narratives/tropes preserved in cultural memory that mainly have been transmitted by literary and visual art history. These practices are still alive today through a contemporary Hungarian artwork, Szabolcs Süli-Zakar’s video installation Sisyphus. The experimental artistic approach shows the myth of Sisyphus, which embodies certain insights of existentialism and the absurd, through reappropriation, becoming a specific metacommentary on aesthetic communication and cognition. It also addresses productive expression and reception, while condemned to eternal repetition and the inaccessibility of transcendental sign and meaning.